Wellness Sanctuary Sebagai Alternatif Penyembuhan Masyarakat Urban di Kabupaten Badung: Bahasa Indonesia - Arya Duta Harjono; I Ketut Sugihantara; I Made Suniastha Amerta (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
Throughout human history living alongside nature and culture, humans have sought peace and a greater understanding of the emotional feelings of life. Humans sometimes forget how the well-being of physical and spiritual life is always related. The reality that occurs in current conditions is that humans live in a society that does not guarantee a healthy environment. This aspect is part of the balance of human health, namely Wellness. In order to maintain the balance of these conditions, humans must be able to adapt in maintaining the physical and mental conditions of humans to their environment. Today, needs in urban areas such as Badung Regency are full of activities that can cause physical and mental fatigue. There needs to be a safe room that can provide good care for the community so they can find a way out in dealing with problems like this. It is hoped that the Wellness Sanctuary building in Badung Regency can become a safe space for clients who want to get peace and comfort. Assisting clients in solving emotional and psychological problems by finding the roots of the problems experienced by sharing stories through experiences and overcoming these mental problems.